1991
DOI: 10.1007/bf02336955
|View full text |Cite
|
Sign up to set email alerts
|

Genetic transmission of migraine without aura: A study of 68 families

Abstract: 68 randomly selected patients with migraine without aura (M) and 4 generations of their relatives (N = 394) were studied in order to probe the genetic hypothesis of migraine. Significantly more of the probands were women and M was significantly more frequent among female relatives. Earlier onset was commoner among male probands. A genetic component of M is indicated by the very high frequency of at least one affected relative (85.3%) and by a disease prevalence that is similar among both first and second degre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

1995
1995
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 8 publications
(9 reference statements)
1
12
0
Order By: Relevance
“…Unfortunately it is much less clear if these types of migraine are inherited. Previous family studies have suggested a genetic factor based on a frequent family history of migraine 2 3 4 5 6 7 8 9 10 11 12 13. The 16-21% prevalence of migraine in the general population, however, may cause this simply by chance 14 15.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Unfortunately it is much less clear if these types of migraine are inherited. Previous family studies have suggested a genetic factor based on a frequent family history of migraine 2 3 4 5 6 7 8 9 10 11 12 13. The 16-21% prevalence of migraine in the general population, however, may cause this simply by chance 14 15.…”
Section: Introductionmentioning
confidence: 99%
“…The family studies also have several shortcomings. Most important are the lack of direct interview of relatives,2 3 4 5 6 7 8 9 10 11 12 13 selection of clinic populations,2 3 4 5 6 7 8 9 10 11 12 13 and lack of distinction between types of migraine 2 3 4 5 6 7 8 9 1012. More valid is the genetic-epidemiological approach used in two previous studies 16 17.…”
Section: Introductionmentioning
confidence: 99%
“…All subsequent studies concurred that relatives of probands with migraine have a higher disease risk. A very high percentage, 85%, of first-degree relatives affected with migraine was found by D'Amico et al [4]. In two studies of the disease risk in relatives of migraine probands, Russell et al [5,6] calculated that the risk for first-degree relatives was 3-fold greater in probands with migraine without aura, and 2-fold greater for probands with migraine with aura.…”
Section: Pasquale Montagnamentioning
confidence: 97%
“…they considered migraine to be a multifactorial disease. D'Amico et al [4] considered migraine to be a disease with "sex-limited" transmission, meaning that environmental or genetic factors related to the sex of the proband modify the expression of the disease, which however is autosomal and otherwise conforms to regular mendelian rules. This is a rather useful concept, which explains the overall higher prevalence of migraine among women in all age groups except pre-pubertal children.…”
Section: Pasquale Montagnamentioning
confidence: 99%
“…Alternatively, familial occurrence of migraine may represent chance clustering of this highly prevalent disease. Family and twin studies have produced conflicting results with respect to the mode of inheritance of migraine (Allan 1928;Goodell et al 1954: Dalsgaard-Nielsen 1965Barolin and Sperlich 1969;Baler 1985;Devoto et al 1986;D'Amico et al 1991;Russell et al 1993;Mochi et al 1993;Lucas 1977;Ziegler et al 1975). This confusion is at least partly a result of methodological differences and shortcomings (Russell et al, 1993;Haan et al 1994).…”
Section: Introductionmentioning
confidence: 94%